Beacon of hope - Sumi, Sabiha Mahmud (Dhaka : ASA, 2010)
On the activities of Association for Social Advancement, microfinance institution in Bangladesh.
Includes bibliographical references.
Keywords: Association for Social Advancement (Dhaka, Bangladesh); Microfinance -- Bangladesh; Financial institutions -- Bangladesh